Qualitative study exploring stakeholder perspectives on the use of early MRI in wrist injury pathways in the UK NHS - Benjamin John Floyd Dean; Helen Hedley; Tim Stephens; Edward Sellon; Nicholas Riley; Liz Baird; Francine Toye; Sam Gidwani; Stephen Lipscombe; Ramesh Chennagiri; David Lawrie; Eoghan Donnelly; et al. (BMJ Open)
Objectives Early MRI use varies in the management of acute wrist injuries in the UK, with only a minority of National Health Service (NHS) centres being able to offer this to patients. In this study, we aim to explore the perspectives of staff and patients on the use of early MRI in the management of wrist injuries.Design This is a cross-sectional qualitative study using semistructured, face-to-face and remote interviews. Interviews were audio recorded, transcribed verbatim and analysed using thematic analysis.Setting 10 NHS Trusts in the UK.Participants We interviewed a sample consisting of 37 NHS staff members and 21 patients.Results We analysed the data into three overarching themes. The first theme described the negative impact of wrist injuries on both staff and patients. Staff reported an uncomfortable feeling that they had ‘short-changed’ patients with older non-MRI based pathways, and that the consequences of missing a scaphoid fracture could be a ‘horrible thing’ for patients. The second theme described how early MRI was perceived as a ‘win for everyone’. For patients, the win encompassed the relief of a speedy diagnosis which helped them to get better. Staff saw early MRI as a win because it ‘revolutionised care’ and ‘reduced the clinic footprint’. The final theme defined the key ingredients of delivering an early MRI pathway: a simple pathway with clear accountability, timely access to MRI and prompt reporting of results, a safe pathway with safety nets to avoid patients being lost, data and audit of the time to MRI and definitive treatment, bottom-up engagement, clear communication and looking after your team.Conclusions Our findings contribute to a better understanding of stakeholders’ perspectives on wrist injury pathways in the UK NHS.